Epidermal growth factor receptor signaling intensity determines intracellular protein interactions, ubiquitination, and internalization - Schmidt, Mirko H. H. (National Academy of Sciences, 2003)
Ligand activation of the epidermal growth factor receptor (EGFR) causes the binding of Cbls, which leads to EGFR polyubiquitination and internalization through endophilin complexes that contain the adaptor protein SH3-domain encoding, expressed in tumorigenic astrocytes/Cbl-interacting protein of 85 kDa/regulator of ubiquitous kinase (SETA/CIN85/Ruk). In cells grown at high density, high levels of SETA interfered in the recruitment of Casitas B-lineage (Cbl) proteins to the EGFR and reduced its polyubiquitination, suggesting that SETA has a regulatory function in the formation of the EGFR–Cbl–endophilin complex and in EGFR down-regulation. In a situation where there is EGFR signaling but no internalization or down-regulation, as is the case with the EGFR with exons 2–7 deleted (ΔEGFR) oncogene, these proteins were absent altogether. By using mAb 806, which recognizes an EGFR-activation state and preferentially immunoprecipitates ΔEGFR, we show that ΔEGFR did not interact with Cbls, SETA, or endophilin A1, providing a mechanistic explanation for its lack of internalization. As would be expected by the absence of Cbl proteins in the ΔEGFR complex, the mutant receptor was also not polyubiquitinated. The intracellular C terminus and tyrosine autophosphorylation pattern of ΔEGFR are similar to wild-type EGFR, but it signals at a lower intensity as determined by levels of EGFR phosphotyrosine. To test the implication that the lack of interaction with the Cbl–SETA–endophilin complex is because of differences in signal intensity, EGFR-expressing cells were treated with tyrphostin AG1478 EGFR inhibitor. Attenuation of wild-type EGFR signal to levels similar to that found in ΔEGFR resulted in the dissociation of SETA and Cbl proteins and a concomitant attenuation of receptor internalization.